Multi-Omics Analysis of MCM2 as a Promising Biomarker in Pan-Cancer - Yuan, Jing; Lan, Hua; Huang, Dongqing; Guo, Xiaohui; Liu, Chu; Liu, Shuping; Zhang, Peng; Cheng, Yan; Xiao, Songshu (Frontiers in Cell and Developmental Biology, 2022)
Minichromosome maintenance 2 (MCM2) is a member of the MCM family of proteins that mainly regulates DNA replication and the cell cycle and is involved in regulating cancer cell proliferation in various cancers. Previous studies have reported that MCM2 plays a pivotal role in cell proliferation and cancer development. However, few articles have systematically reported the pathogenic roles of MCM2 across cancers. Therefore, the present pan-cancer study was conducted. Various computational tools were used to investigate the MCM2 expression level, genetic mutation rate, and regulation mechanism, immune infiltration, tumor diagnosis and prognosis, therapy response and drug sensitivity of various cancers. The expression and function of MCM2 were examined by Western blotting and CCK-8 assays. MCM2 was significantly upregulated in almost all cancers and cancer subtypes in The Cancer Genome Atlas (TCGA), and was closely associated with tumor mutation burden, tumor stage, and immune therapy response. Upregulation of MCM2 expression may be correlated with a high level of copy number alterations. MCM2 expression was associated with the infiltration of various immune cells and molecules and markedly associated with a poor prognosis. Western blotting and CCK-8 assays revealed that MCM2 expression was significantly upregulated in melanoma cell lines. Our results also suggested that MCM2 promotes cell proliferation in vitro by activating cell proliferation pathways such as the AKT signaling pathways. This study explored the oncogenic role of MCM2 across cancers, provided data on the underlying mechanisms of these cancers for further research and demonstrated that MCM2 may be a promising target for cancer immunotherapy.